Seismic Fragility and Behavior of Spherical Pressure Vessels - Öztürk, Sezer; Akgül, Kayahan; Sarı, Ali (ASME, 2021)
Pressurized tanks are vessels that show high impermeability and strength against large internal pressures. These tanks can be used for liquid or gas storage. The internal pressures of the vessels used in gas storage can be at very high levels. These tanks are used in many different areas in the industry. Therefore, human health and life safety is an important parameter. Thus, the design of the tanks to be produced must be suitable for the purpose, as well as the correct analysis and safe usage conditions. Excessive pressure and the temperature difference can lead to explosions that will cause dangerous and many fatal accidents. As a result, domino effects can occur in industrial facilities. For this reason, the risk analysis and seismic behavior of these vessels should be carefully examined. When the performances of past earthquakes are examined, it has been revealed that especially spherical vessels show seismic fragility. Therefore, evaluating the seismic fragility of these vessels is an important issue in regions with high seismic risk. Fragility curves are important tools to evaluate the vulnerability of structures to earthquakes. Within the scope of this study, fragility curves have been created by considering nonlinear time history analyzes and the limited database analyzed for the damage conditions of spherical pressure vessels in earthquakes that occurred in the past years. The curves obtained were interpreted in relation to the ground motion intensity parameter (PGA). In addition, nonlinear time history analyzes of tank models using the Finite Element Method (FEM) have been performed to evaluate the seismic performance of the vessels. Also, the damage data of horizontal tanks were collected and interpreted.
Keywords: Spherical and Horizontal Tank; Pressure Vessels; Seismic Behavior; Seismic Fragility; Finite Element Analysis